Prognostic value of Controlling Nutritional Status score for postoperative complications and biochemical recurrence in prostate cancer patients undergoing laparoscopic radical prostatectomy - Tianyu Xiong; Xiaobo Ye; Guangyi Zhu; Fang Cao; Yun Cui; Liming Song; Mingshuai Wang; Wahafu Wasilijiang; Nianzeng Xing; Yinong Niu (Current Urology)
Abstract. Background. Controlling Nutritional Status (CONUT) score was used for screening the preoperative nutritional status. The correlation between the CONUT score and the prognosis of patients with prostate cancer (PCa) has yet to be elucidated. Herein, we analyzed the prognostic value of CONUT scores in patients with PCa who underwent laparoscopic radical prostatectomy. Materials and methods. Data of 244 patients were retrospectively evaluated. Perioperative variables and follow-up data were analyzed. The patients were categorized into 2 groups according to their preoperative CONUT scores. Postoperative complication and incontinence rates were also compared. The Kaplan-Meier method was used to estimate the median biochemical recurrence-free survival (BCRFS) between the 2 groups. Univariate and multivariate Cox regression analyses were performed to identify the potential prognostic factors for BCRFS. Results. Patients were categorized into the low-CONUT group (CONUT score <3, n = 207) and high-CONUT group (CONUT score ≥3, n = 37). The high-CONUT group had a higher overall complication rate (40.5% vs.19.3%, p = 0.004), a higher major complication rate (10.8% vs. 3.9%, p = 0.013), and longer postoperative length of stay (8 days vs. 7 days, p = 0.017). More fever, urinary infection, abdominal infection, scrotal edema, rash, and hemorrhagic events (all p values < 0.05) were observed in the high-CONUT group. A higher rate of urinary incontinence was observed in the high-CONUT group at 1 (34.4% vs. 13.2%, p = 0.030) and 3 months (24.1% vs. 8.2%, p = 0.023) postoperatively. The high-CONUT group had shorter medium BCRFS (23.8 months vs. 54.6 months, p = 0.029), and a CONUT score ≥3 was an independent risk factor for a shorter BCRFS (hazards ratio, 1.842; p = 0.026). Conclusions. The CONUT score is a useful predictive tool for higher postoperative complication rates and shorter BCRFS in patients with PCa who undergo laparoscopic radical prostatectomy.